Pemberian Hipnopresure terhadap Stres pada Ibu Hamil - Ermi Lilianda Alang; Lucky Herawati; Arwani Arwani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to prove the effect of hypnopressure on stress in pregnant women. The method used was a quasi-experiment with a randomized pre-post-controlled group design. The results showed that respondents in the intervention group experienced a more significant reduction in stress levels. The mean intervention interval until the end of treatment was 10.65, while the control group mean interval was 2.90 (p-value 0.0001). The research concludes that hypnopressure intervention has the effect of reducing stress levels in pregnant women. Keywords: Hypnopressures, Pregnancy, Stress